Rural well-being : From vision to action (The World Bank, 1997)
The Fourth Annual World Bank Conference on Environmentally Sustainable Development was convened in September 1996, with the aim to pursue four key goals:1) poverty reduction; 2) widely shared growth; 3) household, national, and global food security; and 4) sustainable natural resource management. This volume contains the presentations of all the plenary speakers as they are delivered or from written texts. In addition, it contains a summary of each of the thematic and regional roundtables as well as summaries of many of the associated and concurrent events. The volume also reprints the background papers submitted by those who participated in the roundtables. Full text statements from the associated event on Ethics, Values, Spiritually, and Rural Well-Being are also included